Urgensi Peningkatan Sumber Daya Manusia (SDM) dalam Pendidikan - Tanzeh, Ahmad (Ta'allum: Jurnal Pendidikan Islam, 2019)
The realization of good quality ideal human resources, have skills and be able to be highly competitive, become a successful development in education. To produce qualified human resources need an optimal empowerment. The progress of science and technology caused a new paradigm in the effort to achieve the success, namely the competition. The Increasing competition demands increased professional of work quality and work efficiency, so the competitiveness is more competitive. Globalization is able to change the nature of work to make professionalization in all areas of life. One of them gives the impact on the teaching profession. There are demands from the public for teachers to more professional in their work. This paper wants to explain about the urgency of increasing human resources (HR) in education. From this research found: (1) empowerment of human resources in education through; (a) improving the teachers education qualifications and education staff, (b) attending the education process and training, (c) taking courses, (d) improving reading culture, and (e) being active in the mail list; (2) the role of principals in improving the quality of education through; (a) as a leader, (b) as a manager.